FACTORS THAT INFLUENCE STUDENTS’ READINESS IN FACE-TO-FACE LEARNING SETTING IN POST COVID-19 PANDEMIC THROUGH ORDINAL LOGISTIC ROUGH REGRESSION - Sari, Sulistya Umie Ruhmana; Sasongko, Dimas Femy (Proceeding of International Conference on Islamic Education (ICIED); Vol 6 No 1 (2021): Proceeding of International Conference on Islamic Education (ICEID), 2021)
Due to declining trends in Covid-19 in Indonesia, the government of Indonesia is now considering the option of face-to-face learning in educational sector. Based on the current situation, the purpose of this study is to identify the influencing factor of students’ readiness in face-to-face learning post Covid-19 pandemic. Proposed in this study through ordinal logistic rough regression method, the variables that affect the level of students’ readiness in preparing face-to-face learning are: (1) Education Unit Activity Plan and Budget (RKAS) related in funding from socialization activities to the provision of health and hygiene facilities and infrastructure (X1), (2) Supporting facilities to support face-to-face learning in Covid-19 period (X2), (3) Agreement between the school and the school committee (X3), (4) Vaccinations for the entire academic community (X4), (5) Organizing of the Covid-19 task force (X5), (6) Regulation to close cafeteria and to forbid any extracurricular activities (X6), and (7) Guidelines in dividing classroom into small groups, room layout with a minimum distance of 1.5 meters, and one-way traffic direction in hallways/corridors and stairs (X7). The results of the analysis obtained the strength value or association as well as the coefficient of determination in the regression, the Cox and Snell value of 0.843 (84.3%), Nagelkerke's value of 0.766 (76.6%) and Mc Fadden's value of 0.748 (74.8%).